1991
DOI: 10.1017/s0033291700022224
|View full text |Cite
|
Sign up to set email alerts
|

MRI in schizophrenia: basal ganglia and white matter T1 times

Abstract: SYNOPSISThe T1 relaxation time of the basal ganglia (putamen, globus pallidus and head of caudate) and of the frontoparietal centrum semiovale was compared between 49 schizophrenic patients and 36 healthy controls. Previous reports of increased T1 time in the basal ganglia were not confirmed, and group differences were not detected within the white matter. Within patients T1 values could not be related to tardive dyskinesia or other clinical features. Normal variation seen in basal ganglia T1 times is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The short echo time and long TR of our sequences ensured that T " and T # variations of up to 20 % would only result in a 2 % change in our metabolite concentrations. The T " and T # variations reported in schizophrenia (Harvey et al 1991 ;Pfefferbaum et al 1999) are 5 % and therefore , temporal lobe epilepsy and no psychosis ; , temporal lobe epilepsy and psychosis) is compared with normal controls.…”
Section: Discussionmentioning
confidence: 97%
“…The short echo time and long TR of our sequences ensured that T " and T # variations of up to 20 % would only result in a 2 % change in our metabolite concentrations. The T " and T # variations reported in schizophrenia (Harvey et al 1991 ;Pfefferbaum et al 1999) are 5 % and therefore , temporal lobe epilepsy and no psychosis ; , temporal lobe epilepsy and psychosis) is compared with normal controls.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the characterization of the normal anatomical variation in T 1 values throughout the brain, no consistent differences between patients or controls have been found. Neither has any relationship between symptom severity or the occurrence of tardive dyskinesia with T 1 been demonstrated (Harvey et al, 1991).…”
Section: Schizophreniamentioning
confidence: 97%
“…Buckley P et al found schizophrenia patients showed more prolonged T2 relaxation times in the right putamen and globus pallidus than did control subjects, but no significant difference in T2 values was found between patients with and without TD [14]. Harvey et al also didn’t find significant differences in the T1 relaxation time of the basal ganglia between schizophrenia patients with and without TD [15]. Thus, the previous results of neuroimaging studies investigating basal ganglia for TD were still controversial, and the pathophysiologic mechanism of TD may involve other brain areas.…”
Section: Introductionmentioning
confidence: 99%